2020
DOI: 10.2147/ndt.s273045
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Prevalence and Predictors of Postpartum Depression Among Male Partners Who Came to Postnatal Follow-up Clinic with Their Partner in Selected Public Health Centers of Wolaita Zone, Ethiopia, 2019</p>

Abstract: Background: Paternal postpartum depression is a serious public health problem which has a significant effect on mortality and morbidity level. Its effect is not limited to the partner, but it also affects the family, the marital relationship and development of the child. Therefore, this study was planned to assess the prevalence and predictors of paternal postpartum depression among accompanying partners in selected public health centers of Wolaita Zone, Ethiopia. Methodology: An institution-based cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 35 publications
0
15
0
2
Order By: Relevance
“…Only fathers were the research subjects in 10 of the 15 studies, 23,25,26,30,31,[33][34][35][36][37] while couples were the study subjects in the remaining studies. 24,27,28,32…”
Section: Description Of Study Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only fathers were the research subjects in 10 of the 15 studies, 23,25,26,30,31,[33][34][35][36][37] while couples were the study subjects in the remaining studies. 24,27,28,32…”
Section: Description Of Study Subjectsmentioning
confidence: 99%
“…The prevalence of PPD in the included studies ranged between 5.7 and 59.8%. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] The pooled prevalence of PPD in fathers was estimated to be 24.06% (95% CI: 19.35, 28.77; ►Fig. 2).…”
Section: Prevalence Of Postnatal Depression the Pooled Prevalence Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported that nearly a quarter (24.1%) of first-time new fathers had depressive symptoms in China (Cui et al, 2020). The impact of PPD includes distress, sleep difficulties, poor marital relationship, increased suicide risk, and high risk of the child developing behavioral and emotional problems (Alghamdi et al, 2020; Markos & Arba, 2020 Kamalifard et al, 2018; Nishimura et al, 2015).…”
mentioning
confidence: 99%
“…Given that the transition to paternity may be complex and have negative impact on new fathers’ mental health (Markos & Arba, 2020), there is a need to explore the factors contributing to PPD symptoms among new fathers. The objectives of this study were to examine a set of hypothesized paths using perceived stress, neuroticism, and psychological inflexibility to predict depressive symptoms.…”
mentioning
confidence: 99%